Communication, Digital Marketing, and Health.: The image of influencer with a social well-being purpose. - Jiménez Marín, Gloria; Fernandez-Osso Fuentes, Maria (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
The growing use of digital formats in the Spanish advertising system has contributed to a drastic change in marketing, so influencers are increasingly in demand for brand strategies. The objectives are to highlight the prescription that these profiles represent and to discover if they affect the work scheme of agencies, from the marketing plan to strategic planning, creativity, and media, thus assuming a structural element. The methodology combines qualitative and quantitative methods: in-depth interviews, a mass survey, and a Delphi method. The results show the important role of these social profiles for society, end users and communication and marketing companies.